2017
DOI: 10.3389/fnagi.2017.00080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging in Multisensory Integration: A Systematic Review

Abstract: Multisensory integration (MSI) is the integration by the brain of environmental information acquired through more than one sense. Accurate MSI has been shown to be a key component of successful aging and to be crucial for processes underlying activities of daily living (ADLs). Problems in MSI could prevent older adults (OA) to age in place and live independently. However, there is a need to know how to assess changes in MSI in individuals. This systematic review provides an overview of tests assessing the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
149
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 102 publications
(411 reference statements)
13
149
3
Order By: Relevance
“…Older adults appear to benefit more from multisensory enrichment in their environment than younger adults (Berard et al, 2012;de Dieuleveult et al, 2017;Deshpande and Zhang, 2014;Diederich et al, 2008;Townsend et al, 2006). However, there is also some evidence that older adults have trouble ignoring clearly irrelevant or unreliable sensory information; they use all environmental information even when it is disrupted or non-informative (distractors) (Berard et al, 2012;de Dieuleveult et al, 2017;Eikema et al, 2014;McGovern et al, 2014;Teasdale et al, 1991). In general, when performing various tasks, older adults tend to take more time, to be less accurate, and to be more variable than younger adults (de Dieuleveult et al, 2017;DeLoss et al, 2013;Guerreiro et al, 2014Guerreiro et al, , 2015Hugenschmidt et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Older adults appear to benefit more from multisensory enrichment in their environment than younger adults (Berard et al, 2012;de Dieuleveult et al, 2017;Deshpande and Zhang, 2014;Diederich et al, 2008;Townsend et al, 2006). However, there is also some evidence that older adults have trouble ignoring clearly irrelevant or unreliable sensory information; they use all environmental information even when it is disrupted or non-informative (distractors) (Berard et al, 2012;de Dieuleveult et al, 2017;Eikema et al, 2014;McGovern et al, 2014;Teasdale et al, 1991). In general, when performing various tasks, older adults tend to take more time, to be less accurate, and to be more variable than younger adults (de Dieuleveult et al, 2017;DeLoss et al, 2013;Guerreiro et al, 2014Guerreiro et al, , 2015Hugenschmidt et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…It has been shown that aging influences sensory integration (for a review, see de Dieuleveult et al, 2017). Older adults appear to benefit more from multisensory enrichment in their environment than younger adults (Berard et al, 2012;de Dieuleveult et al, 2017;Deshpande and Zhang, 2014;Diederich et al, 2008;Townsend et al, 2006). However, there is also some evidence that older adults have trouble ignoring clearly irrelevant or unreliable sensory information; they use all environmental information even when it is disrupted or non-informative (distractors) (Berard et al, 2012;de Dieuleveult et al, 2017;Eikema et al, 2014;McGovern et al, 2014;Teasdale et al, 1991).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations